Immunological detection of the Weligama coconut leaf wilt disease associated phytoplasma: Development and validation of a polyclonal antibody based indirect ELISA - de Silva, Chamini Kanatiwela-; Damayanthi, Malini; de Silva, Nalin; Wijesekera, Rohana; Dickinson, Matthew; Weerakoon, Devaka; Udagama, Preethi (PLOS one, 2019)
Weligama coconut leaf wilt disease (WCLWD) causes heavy losses in the coconut cultivations of southern Sri Lanka. The in-house developed and validated indirect ELISA was based on specific polyclonal antibodies raised in female New Zealand White rabbits, against partially purified WCLWD associated phytoplasma. This ELISA has the potential to distinguish secA PCR confirmed, WCLWD associated phytoplasma positive palms from phytoplasma free palms at high accuracy (93%) and sensitivity (92.7%), but with marginal specificity (79%). The calculated ELISA cross reactivity index (CRI) values were low for sugarcane white leaf (7%) and sugarcane grassy shoot (8%) infected leaves, but with marked highCRIfor both Bermuda grass white leaf (69%) and areca nut yellow leaf (70%) infected leaves. SecA gene based phylogenetic relationships of the WCLWD associated phytoplasma with these other locally prevalent phytoplasma strains elucidated this immunological cross reactivity, which was further reiterated by virtual restriction fragment length polymorphism analysis. Based on scanning electron microscopy, this study provides additional visual evidence, for the presence of phytoplasmas in WCLWD infected tissues.
Keywords: Weligama coconut leaf wilt disease; phytoplasma; indirect ELISA; polyclonal antibody